Strategi Shadow Teacher Mengatasi Sulit Fokus Pada Anak Berkebutuhan Khusus - Zahra Al Atikah; Az-Zahra, Aura; Fitri Yessi (STAI AL-AMIN, 2024)
This study was motivated by the problem of difficulty focusing on one of the students in one of the Karawang elementary schools. The student is a child with special needs which has an impact on the difficulty of focusing on learning activities. So that these problems attract researchers to research related to these problems. The purpose of this study is to explain the shadow teacher's efforts in overcoming difficulty focusing on children with special needs. The method used in this research is to use a qualitative method with a descriptive approach. The results of the data obtained through observations at school, interviews with tahfidz teachers, then documentation. So that the results obtained in this study include (1) Factors causing one of the students to have difficulty. (2) The shadow teacher's strategy in overcoming student focus difficulties.